The Effect of the Amount of BLT Funds and Distribution Mechanisms on Spending Priorities and Increasing Household Financial Resilience - Wawan Muliawan; Ikhwan Wadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Direct Cash Assistance (BLT) is a government program aimed at helping households meet basic needs and improve financial resilience, especially for low-income communities. This study aims to analyze the effect of the amount of Direct Cash Assistance (BLT) funds and its distribution mechanism on spending priorities and household financial resilience in Bagik Papan Village. The research method used is a quantitative method with a survey approach. Data were obtained by distributing questionnaires to households receiving Direct Cash Assistance (BLT) in Bagik Papan Village. The data analysis technique used multiple linear regression analysis to determine the effect of independent variables on the dependent variable. The results show that the amount of BLT funds has a significant effect on spending priorities and household financial resilience. In addition, the BLT distribution mechanism also has a significant effect on household priorities and financial resilience. Thus, it can be concluded that the amount of funds and the distribution mechanism of BLT have an important role in helping households manage expenses and improve finances. This study is expected to be a consideration for the government in increasing the effectiveness of BLT distribution policies.